2022
DOI: 10.3390/nu14153088
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Content in Cereal-Based Products Sold in Italy: How Far Are We from the Global Benchmarks?

Abstract: Reformulation of food products is one of the measures needed for reducing salt consumption. Accordingly, the World Health Organization (WHO) recently proposed global sodium benchmarks for different food categories to be used for setting national policies. Therefore, the sodium content of cereal-based products currently sold in Italy was compared with the WHO benchmarks, highlighting those categories primarily needing a reformulation. To this aim, the sodium content and several declarations (i.e., nutrition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…However, in recent years there have been no revisions to the national Greek Food and Drink Code regarding the salt content of processed foods, primarily due to ongoing debate that prioritizes allocating resources towards consumer awareness initiatives. This study provides evidence supporting the need of accelerating food reformulation efforts, with the cerealbased products being of particular interest in the EU countries as showed in previous studies (e.g., [24]). A recent study [25] showed that reducing the salt content of bread, with or without dietary counseling, successfully reduced dietary salt intake without adversely affecting the dietary nutritional quality.…”
Section: Discussionsupporting
confidence: 86%
“…However, in recent years there have been no revisions to the national Greek Food and Drink Code regarding the salt content of processed foods, primarily due to ongoing debate that prioritizes allocating resources towards consumer awareness initiatives. This study provides evidence supporting the need of accelerating food reformulation efforts, with the cerealbased products being of particular interest in the EU countries as showed in previous studies (e.g., [24]). A recent study [25] showed that reducing the salt content of bread, with or without dietary counseling, successfully reduced dietary salt intake without adversely affecting the dietary nutritional quality.…”
Section: Discussionsupporting
confidence: 86%
“…If all pre-packaged foods met WHO global sodium benchmarks, the average sodium intake of the Chinese population would be reduced by 13.9% [38]. However, achieving this goal means that approximately 46.9% of Chinese packaged food needs to be reformulated [38]; this result is similar to the study by Martini et al [40], in which they found the sodium content of most of the items of cereal-based products currently sold on the Italian market is much higher than sodium benchmarks. These results indicate that further efforts are needed globally to reduce the sodium content in pre-packaged foods.…”
Section: Discussionsupporting
confidence: 77%
“…Authors attributed these disagreements between the two FOPNL to the different aspects considered for the definition of the healthiness of the products: while Nutri-Score has a nutrient-based scheme for the calculation of the different values, NOVA does not profile nutrients, but just the processing. This means that, for example, the presence of high amounts of salt or sugars in breakfast cereals-as also confirmed by data from our group [11,21]-are differently taken into account by Nutri-Score and NOVA algorithms, i.e, low Nutri-Score and minimally processed items. On the contrary, the presence of industrial ingredients and additives, which classifies the product as "not healthy" by the NOVA system, is not considered for the Nutri-Score.…”
Section: Discussionsupporting
confidence: 68%